ORFIL: Cocopeat–Rice Straw Air Filter for Reducing Motorcycle Exhaust Emissions - Muhamad Naufal Muzhaffar; Dafa Arkananta Saputro; Alawi Hadad El Shirazy; M. Rizkie Akbar Gumilar; Kenzie Abiyyu Pranaja; Agung Taufik (GLOBAL SCIENTS PUBLISHER, 2026)
The increasing number of motorcycles in Indonesia contributes to air pollution, including exposure to particulate matter and ultrafine particles that may affect human health (Schraufnagel, 2020; Masruroh, 2015). This study developed and evaluated ORFIL, a natural air filter made from cocopeat (coconut husk waste) and rice straw, to reduce motorcycle exhaust emissions. The filter material was prepared by dehydrating 70 g cocopeat and 70 g straw for 48 hours, grinding each into coarse powder, mixing them, and packing the mixture inside a factory filter frame using tulle fabric as a retaining layer. Emission performance was tested on one motorcycle (motorcycle X) by comparing the factory-installed foam filter and ORFIL using measured exhaust parameters (CO, HC, CO₂, and O₂). The ORFIL filter produced lower emissions than the factory filter: CO decreased from 0.04% to 0.027%, HC decreased from 19 ppm to 15 ppm, and CO₂ decreased from 0.6% to 0.48%, while O₂ increased from 20.41% to 22.2%. These results indicate that cocopeat and rice straw have practical potential as low-cost natural filter media, consistent with prior findings on coconut fiber and straw-based filtering materials (Lay & Pasang, 2003; Wahyuningrum et al., 2014; Surjosatyo, 2020).